Proposed new interior design for Kolej Cempaka Sari Student Centre at Dewan Cempaka Sari UiTM Seri Iskandar Perak Darul Ridzuan / Raja Suraijah Raja Sahar - Raja Sahar, Raja Suraijah (Faculty of Architecture, Planning and Surveying, 2011)
Final project of Diploma in Interior Design is a manifestation towards the student’s knowledge about the whole aspect of an on interior design that had been learnt from basic to the final presentation on the design purpose. The project that had been chosen for the final project is to Proposed Interior Design Scheme Of Students Centre for kolej Cempaka Sari at UITM Seri Iskandar Perak Darul Ridzuan.This project was followed by a few stage of progress. First is to collect information as much a possible about our client’s background,archievement,organization and client mission and vision. Then it was followed by a strategic location as proposed site. Every stage is include with presentation. The stage goes by proposal stage the followed by planning stage and lastly final presentation. Proposed Students Centre is to attract users, mostly on students uitm to spend time. Mostly, students have a hard time to study because of surrounding environment and not enough time to their study learning at studio and class. The centre is design to single spacing for facilities at students.